Effect of Dividend on Stock Market Price: A Panel Data Approach - Shrestha, Purna Man (Management Dynamics, 2020)
Dividend policy is major concern for investor, managers and policy makers. Proper dividend policy helps to achieve the wealth maximization goal of the firm. This study has examined the impact of dividend on stock market price of Nepalese enterprises. For this purpose 33 dividend paying companies listed on NEPSE has been selected as sample. Likewise, this study used unbalance panel data for the period of 2000/01 to 2018/19. Breusch and Pagan Lagrangian multiplier test concluded that Pooled regression model is not appropriate and Hausman test concluded that Random Effect model is not appropriate for the data used in this study. Thus, this study adopted Fixed Effect model to analyze the impact of dividend on stock market price. This study concluded that there is significant impact of dividend on stock market price of Nepalese enterprises after controlling return on equity, earnings per share and return on equity. Finally, this study concluded that cash dividend has significant negative and stock dividend has significant positive impact on stock market price of Nepalese enterprises.